Pengaruh Latihan Konvensional dan Imagery terhadap Hasil Latihan Tendangan Sabit Atlet Kategori Tanding di Perguruan Silat ASAD Kabupaten Wonosobo (Indonesian Journal for Physical Education and Sport, 2021)
The sickle-kick training method applied at the Asad silat school in Wonosobo Regency has not used imagery. The crescent kick imagery training method is needed by athletes to determine the effective and efficient and maximum motion in carrying out these technical movements. The formulation of the research problem 1) Is there an effect of conventional training on improving athlete's sickle kick technique? 2) Is there an effect of imagery training on improving athlete's sickle kick technique? 3) Is there a difference in effect between conventional training and imagery training on improving athlete's sickle kick technique ? The purpose of this study was to determine the effect of imagery training on the sickle kick of athletes at Asad College, Wonosobo Regency. The research method used is using quantitative methods. The research sample used a total sampling of 14 athletes. Methods of data collection using pretest, posttest, and documentation. The research method used in this research is an experimental method with the M-S pattern (Matching Subject Design). Check the validity of the data using the t test. The results of sickle kicks using conventional training methods have increased. The results of the sickle kick using the imagery training method have increased. And there is a significant difference in improvement between conventional and imagery methods. Discussion that the imagery method is more effective and efficient and can maximize the sickle kick technique than the conventional method. Conclusions: 1) There is an effect of conventional training on improving athlete's sickle kick technique. 2) There is an effect of imagery training on improving athlete's sickle kick technique. 3) there is a significant difference between conventional training and imagery training on improving athlete's sickle kick technique. The researcher's suggestion is that coaches in training not only use conventional training methods but also use imagery training methods because athletes can understand effective and efficient technical movements